Experimental Investigation of the Effects of Partial Shading on Photovoltaic Cells’ Electrical Parameters - W. B. Xiao; F. Y. Hu; H. M. Zhang; H. M. Wu (International Journal of Photoenergy)
The short-circuit current (Isc), the open-circuit voltage (Voc), and the maximum power point (VMPP, IMPP) of monocrystalline and multicrystalline silicon solar cells under three kinds of partial shading patterns have been investigated experimentally. The partial shades are, respectively, the nine shelter locations by 1 cm × 1 cm black card, the six shelter locations by 2 cm × 1 cm black card, and the center shelters with isosceles triangle, circle, square, and two rectangles black cards whose areas are 2 cm2. Firstly, the results show that the partial shading causes disproportional high losses on those parameters of both cells but will have a minimal effect on Voc. Secondly, it is found that those parameters of the monocrystalline cell are less dependent on the shading than that of the multicrystalline cell. Thirdly, it is noted that Isc and IMPP of both cells will be decreasing dramatically as a rectangular black shading card with a long side parallel to cell’s finger, compared with that normal to cell’s finger. Finally, it can be seen that the effects of shading on the electrical parameters of both cells will be suppressed when the border lines of shading match the size of the shaded cell.